Predictors of colorectal carcinoma and inflammatory bowel disease in patients with colonic wall thickening. Issue 3 (4th February 2022) - Pothoulakis, Ioannis; Wikholm, Colin; Verma, Vipin; Ahmad, Akram I; Vangimalla, Shiva S; Patel, Harshkumar; Oh, Jae H; Zhao, Alex; Gress, Kyle L; Bovill, John; Deshpande, Nikita; Marquez, Maria; et al.
Abstract: Background and Aim: Colonic wall thickening (CWT) is commonly associated with clinically significant pathologies, but predictive factors of such pathologies are not well known. This study aims to identify the predictors of clinically significant pathologies, such as colorectal carcinoma (CRC) and inflammatory bowel disease (IBD), in patients with CWT. Methods: Subjects with an abnormal abdominal computed tomography (CT) and a follow‐up colonoscopy between 2010 and 2020 were retrospectively reviewed. Patients with CWT in the CT were included and examined in this study. A multivariable logistic regression analysis was performed to assess for factors independently associated with CRC or IBD in these subjects. Receiver operating characteristic (ROC) curve analysis was used to further examine significant parameters in multivariable logistic regression analysis. Results: Among 403 patients with CWT on CT scans who underwent a colonoscopy, 269 subjects who met the inclusion criteria were identified and studied. On multivariable logistic regression models, elevated platelet count, low hematocrit, and localized CWT were found to be independently associated with CRC, while elevated platelet count and younger age were independently associated with IBD. On ROC curve analysis for CRC, area under the curve (AUC) for hematocrit, platelets, and localized CWT was 0.76, 0.75, and 0.61, respectively. On ROC curve analysis for IBD, AUC for age and platelets was 0.90 and 0.69, respectively. Conclusion: Elevated platelet count, low hematocrit, and localized CWT can be potentially used as predictors of CRC in patients with CWT. Elevated platelet count and young age can be used to predict IBD in these patients. Abstract : This study aims to identify predictors of clinically significant pathologies, such as colorectal carcinoma and inflammatory bowel disease (IBD), in patients with colonic wall thickening. Elevated platelet count, low hematocrit, and segmental colonic wall thickening can be potentially used as predictors of colorectal carcinoma in patients with colonic wall thickening. Elevated platelet count and young age can be used to predict IBD in these patients.